Relics of the Kingdom of Srivijaya in Palembang as a Source of Local Historical Learning - Riki Andi Saputro; Akhmad Arif Musadad; Cicilia Dyah Sulistyaningrum Indrawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
History subjects are compulsory subjects as one of the realms of social sciences. Good history learning is learning that is able to foster interest and ability in students in constructing present conditions by associating them with the past to become a topic of historical learning. The relics of the Kingdom of Srivijaya in Palembang as a learning source are one of the alternatives that can be done in integrating local history in historical learning materials, namely by inserting examples of local events or events to then be illustrated and associated with national history. Learning local history by utilizing the relics of the Kingdom of Srivijaya in Palembang as a source of learning is very important for students as a means to get to know and know about events that have occurred in their area. Relics of the Kingdom of Srivijaya in Palembang are Talang Tuo and Karang Anyar Site and Bukit Siguntang to support historical learning in high school in accordance with the material of the Hindu-Buddhist kingdom in Indonesia. The methods used in this study are descriptive qualitative methods with data collection techniques, namely observation, interviews, literature studies, field studies. The results of historical learning research are very important to teach because learning the history of the past in order to carry out a good future life and will instill an attitude of historical awareness towards students.